Moments like diamonds in space: savoring the ageing process through positive engagement with adventure sports. Issue 5 (20th October 2018) - Hickman, Mark; Stokes, Peter; Gammon, Sean; Beard, Colin; Inkster, Allison
ABSTRACT: There are over 10 million people in the United Kingdom aged over 65, a figure predicted to double by 2050. Despite calls for the outdoors to be a focus for health-related physical activity younger adults still tend to be the predominant users of this resource. In an attempt to understand how older adults aged 65+ relate to outdoor adventure sports, data from purposive samples of rock climbers from the north of England ( n = 8) and sea kayakers from the Highlands and Islands of Scotland ( n = 5) were gathered using focus groups and targeted semi-structured interviews. Analysis using Interpretative Phenomenological Analysis and critical friends showed clear links to theory and highlights the notion that older adults with life course commitments to adventurous 'serious leisure' savor the opportunities afforded by growing older. Furthermore, they reject the constant 'pathologization' of the ageing process, emphasising instead its positive and meaningful aspects.